Strategy for Deployment of Integrated Healthy Aging Regions Based Upon an Evidence-Based Regional Ecosystem—The Styria Model - Borrmann, Marcus; Lindner, Sonja; Hofer-Fischanger, Kathrin; Rehb, Robert; Pechstädt, Katrin; Wiedenhofer, Roswitha; Schwarze, Gabriele; Adamer-König, Eva-Maria; Mischak, Robert; Pfeiffer, Karl P.; Harer, Johann; Weinzerl, Katharina; et al. (Frontiers in Medicine, 2020)
In 2013, the European Commission founded the platform European Innovation Partnership on Active and Healthy Aging as a communication and innovation network in this domain. The goal of the current study was the development of an integrated regional ecosystem for active and healthy aging for the region of Styria via a step-by-step co-creation process. A mixed model approach was used to establish an ecosystem for active and healthy aging, which includes macro-, meso- and micro-level stakeholders in the province of Styria, Austria. Based on the results, eight recommendations for the deployment of a healthy aging region were developed. The visibility and accessibility of healthy aging products and services were evaluated as key factors for innovation in active and healthy aging in the region. Health professionals were identified as major drivers of innovation related to active and healthy aging in Styria. The study presented in this article assessed the capacities for healthy aging in the Styria region and identified the need to improve communication pathways between all levels of the public health system and market.